EFFECTIVE TRAINING METHODS AND TECHNIQUES FOR STUDENTS WITH SPECIAL NEEDS - Иманова, Г.С.; Ескалиева, А.К. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
This article provides an overview of effective teaching methods and techniques specifically designed for students with special needs, as students with special needs require individualized educational approaches to maximize learning outcomes and overall development. The importance of individualized tasks in identifying the unique needs of students is discussed and various strategies used by teachers to meet diverse learning needs are outlined. The article explores the importance of creating a supportive and inclusive learning environment to ensure the success of students with special needs.
Keywords: children with special educational needs; teaching methods and techniques; game technologies; differentiated learning technology